Secondary metabolome and its defensive role in the aeolidoidean Phyllodesmium longicirrum, (Gastropoda, Heterobranchia, Nudibranchia) - Bogdanov, Alexander; Hertzer, Cora; Kehraus, Stefan; Nietzer, Samuel; Rohde, Sven; Schupp, Peter J.; Wägele, Heike; König, Gabriele M. (Beilstein Journal of Organic Chemistry, 2017)
Phyllodesmium longicirrum is the largest aeolidoidean species known to date, and extremely rich in terpenoid chemistry. Herein we report the isolation of a total of 19 secondary metabolites from a single specimen of this species, i.e., steroids 1–4, cembranoid diterpenes 5–13, complex biscembranoids 14 and 15, and the chatancin-type diterpenes 16–19. These compounds resemble those from soft corals of the genus Sarcophyton, of which to date, however, only S. trocheliophorum is described as a food source for P. longicirrum. Fish feeding deterrent activity was determined using the tropical puffer fish Canthigaster solandri, and showed activity for (2S)-isosarcophytoxide (10), cembranoid bisepoxide 12 and 4-oxochatancin (16). Determining the metabolome of P. longicirrum and its bioactivity, makes it evident that this seemingly vulnerable soft bodied animal is well protected from fish by its chemical arsenal.
Keywords: chemical defense; chemoecology; natural compounds; Nudibranchia; Phyllodesmium longicirrum

(untitled) - Wägele, H.; Klussmann-Kolb, A.; Verbeek, E.; Schrödl, M. (Org. Divers. Evol., 2013)

(untitled) - Cattaneo-Vietti, R.; Angelini, S.; Bavestrello, G. (Boll. Malacol., 1993)

(untitled) - Edmunds, M. J. B. (Mar. Sci., 1968)

(untitled) - Edmunds, M. J. A. (Malacol. Bull., 1987)

(untitled) - Wägele, H.; Ballesteros, M.; Avila, C. (Oceanogr. Mar. Biol., 2006)

(untitled) - Klussmann-Kolb, A.; Dinapoli, A.; Kuhn, K.; Streit, B.; Albrecht, C. (BMC Evol. Biol., 2008)

(untitled) - Greenwood, P. G. (Toxicon, 2009)

(untitled) - Burghardt, I.; Schrödl, M.; Wägele, H. (J. Molluscan Stud., 2008)

Evolution in Action - Wägele, H.; Raupach, M. J.; Burghardt, I.; Grzymbowski, Y.; Händeler, K. (Solar powered seaslugs (Opisthobranchia, Gastropoda, Mollusca): incorporation of photosynthetic units: a key character enhancing radiation?, 2010)

(untitled) - Affeld, S.; Kehraus, S.; Wägele, H.; König, G. M. (J. Nat. Prod., 2009)

(untitled) - Bogdanov, A.; Kehraus, S.; Bleidissel, S.; Preisfeld, G.; Schillo, D.; Piel, J.; Brachmann, A. O.; Wägele, H.; König, G. M. (J. Chem. Ecol., 2014)

(untitled) - Bogdanov, A.; Hertzer, C.; Kehraus, S.; Nietzer, S.; Rohde, S.; Schupp, P. J.; Wägele, H.; König, G. M. (J. Nat. Prod., 2016)

(untitled) - Coll, J. C.; Bowden, B. F.; Tapiolas, D. M.; Willis, R. H.; Djura, P.; Streamer, M.; Trott, L. (Tetrahedron, 1985)

(untitled) - Mao, S.-C.; Gavagnin, M.; Mollo, E.; Guo, Y.-W. (Biochem. Syst. Ecol., 2011)

(untitled) - Slattery, M.; Avila, C.; Starmer, J.; Paul, V. J. (J. Exp. Mar. Biol. Ecol., 1998)

(untitled) - Kobayashi, M.; Nakagawa, T.; Mitsuhashi, H. (Chem. Pharm. Bull., 1979)

(untitled) - Kobayashi, M.; Ishizaka, T.; Mitsuhashi, H. (Steroids, 1982)

(untitled) - Iwagawa, T.; Hashimoto, K.; Okamura, H.; Kurawaki, J.-i.; Nakatani, M.; Hou, D.-X.; Fujii, M.; Doe, M.; Morimoto, Y.; Takemura, K. (J. Nat. Prod., 2006)

(untitled) - Hale, R. L.; Leclerq, J.; Tursch, B.; Djerassi, C.; Gross, R. A., Jr; Weinheimer, A. J.; Gupta, K. C.; Scheuer, P. J. (J. Am. Chem. Soc., 1970)

(untitled) - He, H.; Kulanthaivel, P.; Baker, B. J.; Kalter, K.; Darges, J.; Cofield, D.; Wolff, L.; Adams, L. (Tetrahedron, 1995)

(untitled) - Morris, L. A.; Christie, E. M.; Jaspars, M.; van Ofwegen, L. P. (J. Nat. Prod., 1998)

(untitled) - Naz, S.; Kerr, R. G.; Narayanan, R. (Tetrahedron Lett., 2000)

(untitled) - Samimi-Namin, K.; van Ofwegen, L. (ZooKeys, 2016)

(untitled) - Anta, C.; González, N.; Rodríguez, J.; Jiménez, C. (J. Nat. Prod., 2002)

(untitled) - Kobayashi, M.; Hayashi, T.; Nakajima, F.; Mitsuhashi, H. (Steroids, 1979)

(untitled) - Demarco, P. V.; Farkas, E.; Doddrell, D.; Mylari, B. L.; Wenkert, E. (J. Am. Chem. Soc., 1968)

(untitled) - Kobayashi, M.; Kanda, F.; Rao, C. V. L.; Kumar, S. M. D.; Trimurtulu, G.; Rao, C. B. (Chem. Pharm. Bull., 1990)

(untitled) - Raju, B. L.; Subbaraju, G. V.; Reddy, M. C.; Rao, D. V.; Rao, C. B.; Raju, V. S. (J. Nat. Prod., 1992)

(untitled) - Ishitsuka, M. O.; Kusumi, T.; Kakisawa, H. (Tetrahedron Lett., 1991)

(untitled) - Shen, S.; Zhu, H.; Chen, D.; Liu, D.; van Ofwegen, L.; Proksch, P.; Lin, W. (Tetrahedron Lett., 2012)

(untitled) - Kobayashi, M.; Hirase, T. (Chem. Pharm. Bull., 1990)

(untitled) - Kusumi, T.; Yamada, K.; Ishitsuka, M. O.; Fujita, Y.; Kakisawa, H. (Chem. Lett., 1990)

(untitled) - Gross, H.; Kehraus, S.; Nett, M.; König, G. M.; Beil, W.; Wright, A. D. (Org. Biomol. Chem., 2003)

(untitled) - Gross, H.; Wright, A. D.; Beil, W.; König, G. M. (Org. Biomol. Chem., 2004)

(untitled) - Bowden, B. F.; Coll, J. C.; Willis, R. H. (Aust. J. Chem., 1982)

(untitled) - Bowden, B. F.; Coll, J. C.; Heaton, A.; König, G. M.; Bruck, M. A.; Cramer, R. E.; Klein, D. M.; Scheuer, P. J. (J. Nat. Prod., 1987)

(untitled) - Bowden, B. F.; Coll, J. C.; Mitchell, S. J.; Stokie, G. J. (Aust. J. Chem., 1979)

(untitled) - Bernstein, J.; Shmeuli, U.; Zadock, E.; Kashman, Y.; Néeman, I. (Tetrahedron Lett., 1974)

(untitled) - Kashman, Y.; Zadock, E.; Néeman, I. (Tetrahedron, 1974)

(untitled) - Miyaoka, H.; Taira, S.; Mitome, H.; Iguchi, K.; Matsumoto, K.; Yokoo, C.; Yamada, Y. (Chem. Lett., 1996)

(untitled) - Iwagawa, T.; Hashimoto, K.; Yokogawa, H.; Okamura, H.; Nakatani, M.; Doe, M.; Morimoto, Y.; Takemura, K. (J. Nat. Prod., 2009)

(untitled) - Feller, M.; Rudi, A.; Berer, N.; Goldberg, I.; Stein, Z.; Benayahu, Y.; Schleyer, M.; Kashman, Y. (J. Nat. Prod., 2004)

(untitled) - Bergmann, W.; McLean, M. J.; Lester, D. (J. Org. Chem., 1943)

(untitled) - Ciereszko, L. S.; Johnson, M. A.; Schmidt, R. W.; Koons, C. B. (Comp. Biochem. Physiol., 1968)

(untitled) - Wardroper, A. M. K.; Maxwell, J. R.; Morris, R. J. (Steroids, 1978)

(untitled) - Rampen, S. W.; Volkman, J. K.; Hur, S. B.; Abbas, B. A.; Schouten, S.; Jameson, I. D.; Holdsworth, D. G.; Bae, J. H.; Damsté, J. S. S. (Org. Geochem., 2009)

(untitled) - Kusumi, T.; Igari, M.; Ishitsuka, M. O.; Ichikawa, A.; Itezono, Y.; Nakayama, N.; Kakisawa, H. (J. Org. Chem., 1990)

(untitled) - Leone, P. A.; Bowden, B. F.; Carroll, A. R.; Coll, J. C.; Meehan, G. V. (J. Nat. Prod., 1993)

(untitled) - Huang, C.-Y.; Sung, P.-J.; Uvarani, C.; Su, J.-H.; Lu, M.-C.; Hwang, T.-L.; Dai, C.-F.; Wu, S.-L.; Sheu, J.-H. (Sci. Rep., 2015)

(untitled) - Koh, M.; Iwanaga, T.; Hatanaka, M.; Nakano, A.; Morihara, K.; Takemura, K. (Biosci., Biotechnol., Biochem., 2000)

(untitled) - Yan, P.; Deng, Z.; van Ofwegen, L.; Proksch, P.; Lin, W. (Chem. Biodiversity, 2011)

(untitled) - Tanaka, J.; Yoshida, T.; Benayahu, Y. (Galaxea, 2005)

(untitled) - McFadden, C. S.; Alderslade, P.; van Ofwegen, L. P.; Johnsen, H.; Rusmevichientong, A. (Invertebr. Biol., 2006)

(untitled) - McFadden, C. S.; France, S. C.; Sanchez, J. A.; Alderslade, P. (Mol. Phylogenet. Evol., 2006)

(untitled) - Fenical, W. (J. Nat. Prod., 1987)

(untitled) - Ne'eman, I.; Fishelson, L.; Kashman, Y. (Toxicon, 1974)

(untitled) - Coll, J. C.; La Barre, S.; Sammarco, P. W.; Williams, W. T.; Bakus, G. J. (Mar. Ecol. Prog. Ser., 1982)

(untitled) - Coll, J. C. (Chem. Rev., 1992)

(untitled) - La Barre, S. C.; Coll, J. C.; Sammarco, P. W. (Biol. Bull. (Woods Hole, MA, U. S.), 1986)

Handbook of Marine Natural Products - Pawlik, J. R. (Antipredatory defensive roles of natural products from marine invertebrates., 2012)

(untitled) - Brand, J. G.; Bryant, B. P.; Cagan, R. H.; Kalinoski, D. L. (Brain Res., 1987)

(untitled) - Oike, H.; Nagai, T.; Furuyama, A.; Okada, S.; Aihara, Y.; Ishimaru, Y.; Marui, T.; Matsumoto, I.; Misaka, T.; Abe, K. (J. Neurosci., 2007)

(untitled) - Ferchmin, P. A.; Pagán, O. R.; Ulrich, H.; Szeto, A. C.; Hann, R. M.; Eterović, V. A. (Toxicon, 2009)

(untitled) - Rohde, S.; Schupp, P. J. (J. Exp. Mar. Biol. Ecol., 2011)

(untitled) - Rohde, S.; Gochfield, D. J.; Ankisetty, S.; Avula, B.; Schupp, P. J.; Slattery, M. (J. Chem. Ecol., 2012)